Impact of Natural Disasters on Water and Soil in the Northern Gaza Strip، Case Study Umm Al-Nasr Village "Bedouin Village" - Muslim, Alaa Mahmoud; Al-Mughair, Mohammed Mohammed; Al Agha, Mohammed Ramadan (Journal of Risk and Crisis Management, 2019)
The study aimed to focus on the suffering of the people of Umm al-Nasr village by studying the impact of disasters on water and soil in the village of Umm al-Nasr، and to identify the levels of pollution that hit the groundwater in the village، And analysis of reports of samples of the soil that was bombed by the Israeli occupation in the northern Gaza Strip during the war in 2014 with the concentration on the soil and water of the village of Umm al-Nasser، and then to clarify the situation in which the agricultural land that was polluted in the village. The researcher followed the descriptive analytical approach to the sources and reports issued by the ministries and official bodies related to the effects of the environment and scientific studies in the northern Gaza Strip، The results of the analysis of 14 samples of the soil in the northern Gaza Strip، which focus a report on contamination with heavy metals (Ni، Cr، Cu، Mn، Co، Pb) by comparing the standard of the World Health. Analysis Demonstrated improvement in filtration process and improved quality of wastewater treatment despite the presence of contamination in some of the results،Such as nitrates and chlorides are greater than the limits allowed in some wells and the results of ammonia is greater than the permissible limit. The study recommended the need to address environmental life-threatening disasters in the village of Umm al-Nasr، which include pollution of water and soil in scientific ways، as well as adopting the methodology of sustainable development goals for water resources to increase the proportion of wastewater treatment and to overcome the percentage of water losses exceeding 50%،It is also necessary to work on a comprehensive assessment of environmental impacts، including the impact of war on environmental elements in the Gaza Strip، and to take appropriate scientific measures to address the risks.
Keywords: Umm El Nasr Village; Disasters; Heavy Metals; Water; Treatment; Soil